Peningkatan Akurasi Stok Obat melalui Evaluasi Sistem Logistik Menggunakan Root Cause Analysis dan Value Stream Mapping di Rumah Sakit XYZ - Ester Novita Sari; Toguy Abella Br Sirait; Anita Christine Sembiring (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
Hospitals are essential healthcare institutions, making an efficient drug logistics system highly important. This study aimed to identify, analyze, and minimize activities that generated waste or did not provide added value in the pharmacy warehouse of RS. XYZ. Value Stream Mapping was employed to map the actual operational flow and produce a Current Value Stream Map, while Process Activity Mapping was used to classify activities into Value-Added, Non-Value-Added, and Necessary Non-Value-Added categories. Direct observation identified two dominant types of waste, namely Defect and Delay/Waiting, whose root causes were determined through Root Cause Analysis using the 5 Why method and Fishbone Diagram. Several improvement proposals were then developed, including routine Standard Operating Procedure training and additional staff, and illustrated in a Future Value Stream Map representing the improved process flow. Process Cycle Efficiency increased from 2.2% in the Current Value Stream Map to 57.5% in the Future Value Stream Map, an improvement of 55.3%, indicating that the implementation of Value Stream Mapping and Root Cause Analysis effectively reduced waste and improved the efficiency of the drug logistics system in the pharmacy warehouse.